The Effect of Aqueous Extract of Celery Seed on The Glucose Level of Rabbits with Diabetes Experimentally (Journal of Hama University, 2021)
This study was conducted on (50) rabbits, and it aimed to find out the effect of the aqueous extract of celery plant seeds on the level of glucose in rabbits induced diabetes experimentally by alloxan, (5) groups were used, where each group included (10) animals, the first group was left as a witness, while the other groups were injected in Peritoneal cavity with alloxan to induce experimental diabetes, the first group (G1) was provided with water and food only (control), while the second group (G2) was not treated with aqueous extract of celery seed (negative control) and injected with a dose of alloxan (150) mg / Kg. While The aqueous extract of celery seeds was dosed orally at a dose of (60) mg / kg for the third group (G3), and at a dose of (100) mg / kg for the fourth group (G4), and at a dose of (200) mg / kg for the fifth group (G5). The results showed that treatment with aqueous extract of celery seed led to a significant decrease (P≤0.05) in the level of glucose in the groups with induced diabetes compared with the negative control group (G2).